2017
DOI: 10.1523/jneurosci.2969-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity to Hyperpolarizing Inhibition in Mesoaccumbal Relative to Nigrostriatal Dopamine Neuron Subpopulations

Abstract: Midbrain dopamine neurons recorded in vivo pause their firing in response to reward omission and aversive stimuli. While the initiation of pauses typically involves synaptic or modulatory input, intrinsic membrane properties may also enhance or limit hyperpolarization, raising the question of how intrinsic conductances shape pauses in dopamine neurons. Using retrograde labeling and electrophysiological techniques combined with computational modeling, we examined the intrinsic conductances that shape pauses evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(95 citation statements)
references
References 61 publications
18
71
0
Order By: Relevance
“…The strong rebound characteristics of the striosome-inhibited subpopulation of neurons will contribute to a synchronous rebound by allowing fast return to firing after inhibition. However, this characteristic is not ubiquitous among dopamine neurons, as dopamine neurons in the VTA are more variable in their recovery time from inhibition due to the slow A-type potassium current kinetics (Tarfa et al, 2017). Mechanistically, the structure of the striosome-dendron bouquet may contribute to synchrony among dopamine neurons.…”
Section: Function Of Genetically-defined Inhibitory Inputs Onto Snc Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong rebound characteristics of the striosome-inhibited subpopulation of neurons will contribute to a synchronous rebound by allowing fast return to firing after inhibition. However, this characteristic is not ubiquitous among dopamine neurons, as dopamine neurons in the VTA are more variable in their recovery time from inhibition due to the slow A-type potassium current kinetics (Tarfa et al, 2017). Mechanistically, the structure of the striosome-dendron bouquet may contribute to synchrony among dopamine neurons.…”
Section: Function Of Genetically-defined Inhibitory Inputs Onto Snc Nmentioning
confidence: 99%
“…Functionally testing the strength and characteristics of inhibitory inputs onto SNc neurons will allow us to determine which specific inhibitory sources can induce rebound activity. Interestingly, we have previously shown that only certain subpopulations of dopamine neurons contain the intrinsic mechanisms necessary to rebound from inhibition, while other subpopulations lack this feature Tarfa et al, 2017). This suggests that the pause-rebound firing pattern would be limited to a distinct population of dopamine neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Only some of these identified in vivo differences were predicted based on previous studies of diverging intrinsic in vitro properties between distinct DA subpopulations (e.g. rebound delays and pausing) Lammel et al, 2008;Tarfa et al, 2017), while other features, like differences in mean firing rates were surprising and indicated that certain neuronal network properties might override intrinsic differences in excitability. Overall, our study provides a refined functional in vivo landscape of the midbrain DA system embedded in an anatomical context of identified axonal projections.…”
Section: Introductionmentioning
confidence: 91%
“…The functional properties and the emerging diversity of the midbrain dopamine (DA) system have been extensively studied across many different biological scales (Schultz, 2015;Watabe-Uchida et al, 2017). These differences range from the single-cell level, including diverging gene expression profiles (Kramer et al, 2018;Nichterwitz et al, 2016;Poulin et al, 2018;Saunders et al, 2018a;Tiklova et al, 2019), cellular and biophysical properties Lammel et al, 2008;Tarfa et al, 2017), as well as neurotransmitter co-release (Chuhma et al, 2018;Kim et al, 2015b;Tritsch et al, 2012;Zhang et al, 2015), up to different neural circuit affiliations (Beier et al, 2019;Beier et al, 2015;Lammel et al, 2012;Lerner et al, 2015;Menegas et al, 2015;Ogawa et al, 2014;Tian et al, 2016;Watabe-Uchida et al, 2012) and selective task engagement of DA subpopulations in awake behaving rodents (Dautan et al, 2016;de Jong et al, 2019;Duvarci et al, 2018;Gunaydin et al, 2014;Howe and Dombeck, 2016;Keiflin et al, 2019;Lammel et al, 2012;Matthews et al, 2016;Menegas et al, 2018;Menegas et al, 2017;Parker et al, 2016;Patriarchi et al, 2018;Saunders et al, 2018b;Vander Weele et al, 2018;Yang et al, 2018) and non-human primates …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation